2021
DOI: 10.5194/gc-4-11-2021
|View full text |Cite
|
Sign up to set email alerts
|

Volcanoes in video games: the portrayal of volcanoes in commercial off-the-shelf (COTS) video games and their learning potential

Abstract: Abstract. Volcanoes are a very common staple in mainstream video games. Particularly within the action–adventure genres, entire missions (e.g. Monster Hunter: Generation Ultimate, 2018) or even full storylines (e.g. Spyro: The Reignited Trilogy, 2018) can require players to traverse an active volcano. With modern advancements in video game capabilities and graphics, many of these volcanic regions contain a lot of detail. Most video games nowadays have gameplay times in excess of 50 h. The Legend of Zelda: Brea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Authors identified geological and geomorphological features, including active volcanoes, crater lakes, and peninsulas, which were tied to key moments within the game's main narrative. This approach is inspired by McGowan and Scarlett (2021), where geoscientific features are identified in popular commercial video games and then compared to realworld examples. Features and areas that are a necessity for progression, therefore guaranteeing player interaction, are particularly addressed.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Authors identified geological and geomorphological features, including active volcanoes, crater lakes, and peninsulas, which were tied to key moments within the game's main narrative. This approach is inspired by McGowan and Scarlett (2021), where geoscientific features are identified in popular commercial video games and then compared to realworld examples. Features and areas that are a necessity for progression, therefore guaranteeing player interaction, are particularly addressed.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work by Hut et al (2019), McGowan and Scarlett (2021), and Clements et al (2022) illustrates how popular commercial games (including Legend of Zelda: Breath of the Wild and Minecraft) could be used as a form of geoscience communication to promote and educate the wider public, covering topics such as volcanology and palaeontology. If effectively used, commercial video games can become a powerful tool in educational settings and at outreach events, to stimulate geoscientific education and engagement in students.…”
Section: Learning Via Video Gamesmentioning
confidence: 99%
See 3 more Smart Citations